Edentulous patients' knowledge of dental hygiene and care of prostheses - De Castellucci Barbosa, Luciano; Ferreira, Manoela Rejane Maia; De Carvalho Calabrich, Carolina Freire; Viana, Aline Cavalcanti [UNESP]; De Lemos, Maria Catarina Lavigne; Lauria, Roberta Andrade (Wiley, 2008)
Objective: The aim of this study was to analyse denture users' oral care habits with regard to the use of their prostheses. Background: Rehabilitative treatment is only successful when patients are motivated and aware of correct prosthesis use and hygiene. Materials and methods: Questionnaires were distributed to 150 complete denture users at the Federal University of Bahia School of Dentistry, the Esmeralda Natividade Health Center, the Bahian Science Development Foundation and a Salvador nursing home. The questionnaire included information on gender, age, length of prosthesis use, cleaning methods and materials, etc. The data were analysed using EpiInfo version 6 software. The chi-squared test was used for statistical analysis, with a significance level of 5%. Results: Questionnaire results showed that 78% of the subjects, with an average age of 67.3 years, had used the same complete denture for over 5 years. 64% slept with their prostheses and 44% removed them from the mouth only for cleaning. None of the patients interviewed knew anything about brushes designed specifically for complete dentures. 37.3% had a restricted diet and 44% believed that a complete denture would last for more than 10 years. Conclusion: Within the limitations of this study, it was concluded that the edentulous patients surveyed had limited awareness of prosthetic hygiene and long-term oral care despite extended periods of denture use. © 2008 The Authors.
Keywords: Complete dentures; Dental care; Dental habits; Hygiene; Prostheses; toothpaste; adult; aged; attitude to health; chi square distribution; denture; female; human; male; methodology; middle aged; mouth disease; mouth hygiene; patient education; psychological aspect; questionnaire; sleep; Adult; Aged; Aged, 80 and over; Chi-Square Distribution; Denture Cleansers; Denture, Complete; Female; Health Knowledge, Attitudes, Practice; Humans; Male; Middle Aged; Mouth, Edentulous; Oral Hygiene; Patient Education as Topic; Questionnaires; Sleep